2000
DOI: 10.1080/135406000114735
|View full text |Cite
|
Sign up to set email alerts
|

Theory, Practice and Reflection: A pre-service primary mathematics education programme

Abstract: This paper describes a case study investigating the impact of a primary mathematics method programme on pre-service primary teachers' capacity, and willingness to learn and teach mathematics for relational understanding. The programme, a collaborative endeavour between primary schools and university tutors, enables student teachers to practice in an on-going, integrated and consistent manner what they are learning in theory, and to re¯ect on their experiences. The ® ndings from test, questionnaire and intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…However, engaging prospective teachers in thinking skills activities over several months during their training course seems to have changed their views about teaching and learning in general and with respect to teaching mathematics in particular. These findings are consistent with previous literature, which revealed that many teachers tend to teach in the same way in which they were taught as students, either at school or at university (Ball 1988, Borko and Mayfield 1995, Hill 2000, Bruce 2004, Henderson and Rodrigues 2008.…”
Section: Discussionsupporting
confidence: 83%
“…However, engaging prospective teachers in thinking skills activities over several months during their training course seems to have changed their views about teaching and learning in general and with respect to teaching mathematics in particular. These findings are consistent with previous literature, which revealed that many teachers tend to teach in the same way in which they were taught as students, either at school or at university (Ball 1988, Borko and Mayfield 1995, Hill 2000, Bruce 2004, Henderson and Rodrigues 2008.…”
Section: Discussionsupporting
confidence: 83%
“…Ball (1988) has argued that a lack of attention to what teachers bring with them to learning to teach may account for the reason why teachers tend to teach mathematics as they were taught themselves. In Australia, Hill (2000) has explored why mathematics education programmes appear to have only a limited effect on trainee teachers' capacity and willingness to learn and teach mathematics for relational understanding (knowing both what to do and why). She argues that even though trainees are trained to teach for relational understanding they often revert to the instrumental methods they learnt in school.…”
Section: Contextmentioning
confidence: 99%
“…There is research which reports that teachers' prior beliefs can affect knowledge acquisition (Aitken and Mildon, 1991;Calderhead and Robson, 1991;Foss and Kleinsasser, 1996;Johnson, 1994;Mallette et al, 2000;Tillema, 1995) and that they can be resistant to change (Aitken and Mildon, 1991;Foss and Kleinsasser, 1996;Johnson, 1994;Weinstein, 1990, Virta, 2002. There is also research which reports not only stability in student teachers' prior beliefs, but also change from beliefs which can be counterproductive to teaching to beliefs which are more likely to boost learning (Ambrose, 2001;Ackley et al, 1999;Bell, 2001;Dart et al, 1998;Harrington and Hertel, 2000;Hill, 2000;Joram and Gabriele, 1997;Long and Stuart, 2004;McGovern, 2000;Pugalee, 1999;Roberts et al, 2001;Sillman and Dana, 1999;So and Watkins, 2005;Stuart and Thurlow, 2000). In addition, there is research by I would argue that the factor that must have differentiated the outcomes of the above studies is the engagement of student teachers in reflection on their beliefs.…”
Section: The Development Of Cypriot Primary School Teachers' Theoriesmentioning
confidence: 99%
“…The most appropriate qualitative method to use was the interview. According to May (1997) "interview yields rich insights into people's experiences, opinions, aspirations, (Ambrose, 2001;Collier, 1999;Hill, 2000;Long and Stuart, 2004;McGovern, 2000;Russell, 1988;So and Watkins, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation